GREEK IN UKRAINE: RESULTS OF WORK AND PROSPECTS FOR THE DEVELOPMENT OF THE GREEK PHILOLOGY AND TRANSLATION DEPARTMENT AT MARIUPOL STATE UNIVERSITY - Nicas, Arhiris; Macri, Efi (The Modern Higher Education Review, 2018)
The Department of Greek Philology and Translation of Mariupol State University, which celebrates its 20th anniversary this year, functions as the main carrier of teaching, dissemination and spreading of the Greek language and Greek culture, not only for the Ukrainian people, but also for representatives of the Greek Diaspora in the country and, in particular, in the Azov Sea region. The article illustrates the results of the work of the Department of Greek Philology and Translation of Mariupol State University.